Environmental Quality of Residential Elderly in Śląskich Prewar Performers Residential - Szewczenko, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of this article is to focus attention on difficult life situation of the elderly – inhabitants in pre-war housing settlements. The author presents the diagnosis of living conditions of the elderly in housing environment and, moreover, raises the question of elementary possibilities of improvement methods. There is a heavyweight risk of marginalization the elderly inhabitants generated by the proprietary structure of this housing estates, no maintenance and lack of investments, and, moreover, because of the socio-economic situation of the inhabitants. The analysis of these situation was based on researches in 2005–2007 in selected pre-war housing estates. The chosen criteria were based on the other criteria used for research studies of health quality of housing environment, conducted by World Health Organization.